HoBi‐like pestivirus infection leads to bovine death and severe respiratory disease in China. Issue 3 (21st September 2020) - Chen, Meng; Liu, Mengda; Liu, Sidang; Shang, Yingli
Abstract: HoBi‐like pestivirus is an emerging atypical pestivirus in cattle and small ruminants, causing clinical signs similar to those observed in bovine viral diarrhoea virus infections. Natural infection of HoBi‐like pestivirus has been reported in cattle herds and small ruminants in multiple countries in South America, Europe and Asia. However, HoBi‐like pestiviruses were only identified from contaminated bovine serum and small ruminants in China. So far, no clinical cases induced by HoBi‐like pestivirus infection were reported in Chinese cattle herds. Here, for the first time, we reported natural infection of HoBi‐like pestivirus in a cattle herd in China. Sick cattle with severe respiratory and diarrhoea and high fatality rate were found in a beef cattle herd in Shandong province in November 2017. RT‐PCR, viral isolation, sequencing and phylogenetic analysis showed that the primary causative agent was HoBi‐like pestivirus. The isolated HoBi‐like pestivirus strain, SDJN‐China‐2019, shared 94.1%–97.5% homology with the LV168‐20_16RN strain from Brazil in nucleotide of 5′UTR, N pro and E2 while it shared only 88.5%–92.1% homology with Asian HoBi‐like virus strain Th/04‐Khonkaen. Multiple unique mutations of amino acid were observed in N pro and E2 proteins of SDJN‐China‐2019, which were different from that of other reference strains. In summary, this study provides the first evidence of HoBi‐like pestivirus infection in Chinese cattle herds, raising potential threat to the cattle industry in China.